BLENDED LEARNING MODEL IMPLEMENTATION TO IMPROVE CRITICAL THINKING SKILL IN HISTORY LEARNING - Makmur, Tarunasena (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2012)
The focus of the issues that raised in this thesis was motivated by the researcherâ€™s experience based on the preliminary observations result which indicate that the learning process by using only discussions or assignments through e-learning that produces essay without discussion proved to be successful in improving studentsâ€™ critical thinking skills. The discussions developed to promote cooperation among students, while the critical thinking skills was barely touched. Likewise, the assignment through e-learning, although what out come seems good, but it seemed to be a â€œcopy and pasteâ€ work. So it raises the doubts on the assignment result originality. Thus the researchers tought to answer the following research questions: 1) How to plan a blended-learning to improve the critical thinking skills in learning history? 2) How does the implementation of blended-learning models to improve the critical thinking skills in the learning of history? 3) How to overcome the obstacles that rise in blended-learning model implementation in order to improve critical thinking skills? This study used qualitative approach with Classroom Action Research model. The results conclusion included: first, at the planning stage the preparation are syllabus, lecturing events unit, format field notes, observation checklist, as well as the Learning Management System (LMS) by using software moodle provided by the Direktorat TIK UPI. LMS used as an evaluation tool and observation tool of the learning process through e-learning. Second, the implementation of blended learning models could improve the critical thinking skills in learning history through three cycles. Third,. The obstacle emerged in this study was particularly the technical constraints on the essay assignment that must be collected online which is overcome by using a CD.